Prevalence of Sleepwalking: A Systematic Review and Meta-Analysis. - Helen M Stallman; Mark Kohler (PLoS ONE)
Sleepwalking is thought to be a common arousal disorder; however, the epidemiology of this disorder has not yet been systematically examined. A systematic search of MEDLINE, CINAHL, EMBASE, PsycINFO, PubMed, and ScienceDirect was conducted for 'sleepwalking' OR 'somnambulism' in any field, to identify studies that reported the epidemiology of sleepwalking or sleepwalking disorders. Fifty-one studies assessed the prevalence rates of sleepwalking in a total sample of 100 490. The meta-analysis showed the estimated lifetime prevalence of sleepwalking was 6.9% (95% CI 4.6%-10.3%). The current prevalence rate of sleepwalking-within the last 12 months-was significantly higher in children 5.0% (95% CI 3.8%-6.5%) than adults 1.5% (95% CI 1.0%-2.3%). There was no evidence of developmental trends in sleepwalking across childhood. The significant risk of bias across all studies suggests these results should be used cautiously. Further epidemiological research that addresses methodological problems found in studies of sleepwalking to date is needed.